Modeling the Antecedents of Customer Engagement With Health Related Content - Chauhan, Trishala; Sindhu, Shilpa (Indian Journal of Computer Science, 2021)
This paper seeks to study the interrelationship between different variables impacting customer engagement with health-related content. For this ISM approach has been employed. Variables impacting customer engagement are identified from the existing literature and subsequently modeled in the form of a diagraph (ISM Model). Finally, the variables are classified into different categories based on their dependence and driving power using MICMAC Analysis. Seven variables identified from the literature are readable content, usefulness of content, socialization needs, trustworthiness, complete information, subjectivity, and content novelty. These variables are then modeled into a diagraph (ISM model) showing interrelationship among the variables. Three levels of hierarchy are formed. Where the first level is occupied by three variables namely, usefulness of content, socialization needs, and content novelty. The second level is occupied by three more variables, namely, readable content, trustworthiness, and subjectivity. The third level is occupied by one variable, that is, complete information. Using MICMAC analysis content novelty is classified as autonomous variable, usefulness of content and socialization needs were classified as dependent variables, trustworthiness, and subjectivity are classified as linkage variables, readable content, and complete information being classified as independent variables.